Spatial-Based Assessment of Village Development Levels Using Regional Potential Indicators in IV Koto Aur Malintang, West Sumatra - Wita Puspa Dewita; Yurni Suasti (Postgraduate, University of Mataram, 2026)
Village-level development is an essential component of regional planning that emphasizes the sustainable utilization of local potentials. This study aims to assess the level of development across five Nagari in IV Koto Aur Malintang Subdistrict, Padang Pariaman Regency, based on regional potential indicators outlined in the Indonesian Ministry of Home Affairs Regulation No. 12 of 2007. Using a quantitative descriptive approach, the Research analyzes secondary data on natural resources, human resources, institutional capacity, infrastructure, and public facilities. Each indicator was scored according to the official village profiling guidelines to categorize the development potential of each Nagari. The results indicate that the highest natural resource potential lies in the plantation and livestock sectors, particularly in Nagari III Koto Aur Malintang Selatan and Nagari III Koto Aur Malintang Utara. Agricultural potential tends to fall within the moderate-to-low range in most Nagari. In terms of human resources, population density and livelihood diversity vary significantly, influencing disparities in development outcomes. Institutional strength and infrastructure availability also vary across Nagari, with some exhibiting limitations in transportation and health facilities. Overall, development potential is categorized into three groups: high potential (Nagari III Koto Aur Malintang Selatan and Nagari III Koto Aur Malintang Timur), medium potential (Nagari III Koto Aur Malintang Utara and Balai Baiak Malai III Koto), and low potential (Nagari III Koto Aur Malintang). The study highlights the importance of adopting a place-based development approach to reduce inter-Nagari disparities. These findings are expected to inform more contextual, targeted, and sustainable village development planning.